ANALISIS PERAN PEREMPUAN DALAM PERTANIAN DI KECAMATAN RASAU JAYA KABUPATEN KUBURAYA - HUTAJULU, JOSUA PARULIAN (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2015)
Work type separation by gender eroded over the development of human civilization, including in agricultural sector. This research involves 50 respondents from 237 populations of complete couple that own minimum 0,5 Ha of land. This research analyzes women’s contribution in agricultural economy beside as the housewifes. Women’s role (in agricultural economy) divided into two activities, the first activity is pre-harvesting such as land processing, seed/ fertilizer /infrastructure preparation, weeding, pest and disease prevention and watering. The second activity is harvesting and post-harvesting such as crop threshing, harvesting, cleaning, transport, sorting, and marketing. Average time of women’s involvement in agricultural activity is 5,3 hours/workday with average land area 1,26 Ha, which is 2,6 involved labours/workday /5 hours. Women’s contribution in each pre-harvesting activities are, 49,69 % in land processing, 53% in seed/feltilizer preparation, 52,22 % in planting, 52,22 % in fertilizing, 51,53% in weeding, and 54,25% in watering. Women’s contribution in each harvesting and post-harvesting activities are, 50,25% in threshing, 66,25% in harvesting, 33,13% in transporting, 55,22% in cleaning, 52,97% in sorting and 53,00% in marketing. Women have major contribution in almost every pre-harvesting, harvesting and post-harvesting activities, but they have minor contribution in decision making of determining the crop variety (28%), planting schedule (32%), seed and fertilizer procurement (38%), marketing (28%), and farmer group/ foundation suggestion (30%). Those women’s minor contribution is the effect of strong paternalist culture. Keywords : women’s, role, agricultural, economy, workday